Hastings Alumni and Fresno County Bar Association Joint Luncheon with California Supreme Court Justice Wiley Manuel - Watkins, Howard::::::::: (1979)
Howard Watkins introducing Justice Wiley Manuel Howard was chair of the Hastings Alumni-Fresno Chapter